STUDY LITERATURE OF THE EFFECTIVENESS OF AEROBIC GYMNOW TO BLOOD GLUCOSE LEVELS IN PATIENTS DIABETES MELLITUS TYPE 2 (STUDI LITERATUR EFEKTIVITAS SENAM AEROBIK TERHADAP KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELLITUS TIPE 2) - Radiah Ilham; Ramlah Ramlah; Sudirman Sudirman (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Diabetes mellitus is a type of non-communicable disease that can cause high morbidity and mortality. This disease is not a new disease, it's just that it doesn't get enough attention in the community, especially those who have a high risk of suffering from the disease. The purpose of this literature study is to identify recommendations about the effectiveness of aerobic exercise on blood glucose levels in type 2 Diabetes Mellitus patients. This literature search was conducted to find articles that fit the topic through the Google Scholar database using keywords or Keyword aerobics